Nutritional profile, processing potential and food applications of Macrotermes nigeriensis powder: A comprehensive review (Scientia Agropecuaria, 2026)
Macrotermes nigeriensis is increasingly recognized as a nutrient-dense edible insect with significant potential for food and non-food applications. This review synthesizes current evidence on proximate composition, mineral and vitamin content, amino acid and fatty acid profiles, functional properties, and safety considerations of its powder. Existing studies consistently report high levels of protein, essential minerals (Fe, Zn), and vitamin C, together with low concentrations of antinutritional factors. When incorporated into various food matrices (including cakes, biscuits, and fermented cassava beverages) M. nigeriensis powder markedly enhances protein density, micronutrient content, and, in some cases, sensory acceptability. Protein isolates exhibit desirable emulsifying and foaming properties, supporting their potential use in food formulation. Beyond nutrition, the species also provides oils that may serve as unconventional feedstock for biodiesel production. Overall, M. nigeriensis represents a promising sustainable protein resource, but further multidisciplinary investigation is required to support its large-scale utilization. Future research should focus on: (i) long-term safety and toxicological evaluation, (ii) nutrient bioavailability and digestibility, (iii) detailed lipid profiling and its health implications, (iv) standardization of processing and preservation methods, and (v) consumer acceptance and market feasibility beyond endemic regions.